Ceramic modified C / C composite material high-temperature screw and preparation method thereof
By depositing hot carbon on carbon fiber prefabricated body and introducing ultra-high temperature ceramic MC-SIC modifiers, combined with the use of SIC coating, preparing ceramic modified C/C composite materials high temperature screws The problem of insufficient performance in the environment in the ultra -high temperature oxidation of ℃ has achieved excellent mechanical properties and resistance to ablation.
Patent Information
- Application Number
- CN202411477699.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-21
AI Technical Summary
The existing high-temperature screws are insufficient in ultra-high temperature oxidation and ablation environment at 2000 °C, and have a long preparation cycle and are prone to failure, which cannot meet the high-temperature service needs of high-speed aircraft.
The preparation method of high-temperature screws of ceramic-modified C/C composite materials is adopted. By depositing pyrolytic carbon on the carbon fiber preform, it is processed into a C/C cylinder, and reactive infiltration is carried out in a vacuum heat treatment furnace to introduce ultra-high-temperature ceramic MC- SiC modification phase, and finally SiC coating is deposited on the screw surface.
Achieving the structural integrity in the ultra -high temperature oxidation and ablation environment of 2000 ° C, significantly improved the resistance of the ablation, simplified the preparation process, shortened the preparation cycle, and avoided the damage to the fiber by complex procedures and circulating thermal treatment.
Smart Images

Figure CN119330737A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high temperature resistant fasteners, and specifically relates to a ceramic modified C / C composite material high temperature screw resistant to ultra-high temperature of 2000°C and a preparation method thereof. Background Art
[0002] In recent years, with the continuous increase in the flight Mach number of high-speed aircraft, the service temperature of aircraft thermal protection systems has gradually increased and has exceeded 2000 ℃, which has put forward more stringent requirements on the high temperature resistance and service reliability of thermal protection systems. The thermal protection system consists of the aircraft cabin and the surface high temperature resistant heat protection materials. Screw fasteners play a vital role in the connection between the two. Therefore, the development of a new generation of high temperature resistant and high load-bearing screw fasteners has become one of the key factors affecting the high temperature service performance of the thermal protection system. At present, high temperature screws made of refractory alloys as the main component have limited temperature resistance, high density and expansion coefficient, and can no longer meet the needs of the service process of high-speed aircraft.
[0003] Carbon / carbon (C / C) composites have a series of advantages such as low density, low thermal expansion coefficient, high specific strength, and mechanical properties that increase instead of decrease with increasing temperature. They are one of the best materials for fastener screws used in thermal protection systems of high-speed aircraft. Therefore, the use of C / C composites to prepare high-temperature screws has become a feasible alternative. However, C / C composites will experience oxidation weight loss when serving in an oxidizing and ablative environment above 400 °C, which seriously restricts their long-life service in high-temperature environments. Introducing antioxidant and high-temperature resistant ceramics into C / C composites is an effective way to improve the high-temperature oxidation and ablation resistance of C / C screws. Reference 1 "Gao Yong, Wang Jinjin, Cha Bolin et al. Effect of ablation time on ablation mechanism of C / C-SiC composites in hypersonic oxygen-rich environment [J], Journal of Composite Materials, 2023, 40(1): 472-484", needle-punched C / C-SiC composites prepared by the hybrid process of "chemical vapor infiltration + precursor impregnation and pyrolysis" were tested in an oxygen-rich environment. The hypersonic ablation test proved that the introduction of SiC modified phase can generate a SiO2 protective film during the ablation process, which effectively prevents the diffusion of oxidizing components into the matrix and improves the ablation resistance of C / C composites.
[0004] Patent 1 "Dong Yongpeng, Hong Wenhu, Xu Xiaojing, et al. A high-temperature resistant and removable heat-resistant plug structure, CN110834712B [P]. 2021." C / C screws and C / SiC screws are used as high-temperature fasteners in high-temperature resistant and removable heat-resistant plug structures. The screws have a long life and temperature resistance of up to 1500 °C. In document 2 "B. Li, J. Ge, Z. Wu, et al. Damage evolution analysis of C / SiC screwed / bonded hybrid joints based on in-situ micro-CT technique [J], Composites Part A, 2024, 186: 108417", the authors believe that C / SiC screws have good high-temperature mechanical properties and regard them as an important development direction of connection structures.
[0005] However, the existing C / C-SiC and C / SiC high-temperature screw preparation technologies mostly use chemical vapor infiltration processes or precursor impregnation and cracking technologies. The preparation cycle is long and the preparation process is accompanied by multi-cycle cyclic heat treatment links, which can easily damage the screw fibers and cause mechanical properties to deteriorate. In addition, the modified phase of existing C / C screws is mostly SiC ceramics. When the service temperature of the screw exceeds 1700 ℃, the SiO2 protective film generated by in-situ oxidation of SiC will quickly evaporate and fail, which can easily cause catastrophic failure. Therefore, for the thermal protection system of high-speed aircraft, it is urgent to develop a new type of ultra-high temperature screw with a simple preparation process, short preparation cycle, and both mechanical strength and ultra-high temperature anti-oxidation and ablation performance. Summary of the invention
[0006] To solve the above problems, the present invention proposes a ceramic-modified C / C composite material high-temperature screw and a preparation method thereof, which solves the problems of long preparation cycle of screw components prepared by the prior art, insufficient high-temperature resistance of the screws, and easy failure due to ultra-high temperature ablation, and is suitable for an ultra-high temperature oxidation ablation environment of 2000 ℃.
[0007] The first object of the present invention is to provide a method for preparing a ceramic modified C / C composite material high temperature screw, wherein the ceramic modified C / C composite material screw has the ability to withstand a high temperature ablation environment of 2000°C, and specifically comprises the following steps: (1) Depositing pyrolytic carbon on the carbon fiber preform obtained by weaving to obtain a low-density C / C composite material; (2) Cutting the low-density C / C composite material into C / C cylinders, grinding, cleaning and drying; (3) The C / C cylinder is placed in alloy powder for reaction infiltration to introduce multiphase ultrahigh temperature ceramics for modification, and then processed into a standard screw; (4) depositing pyrolytic carbon on the ceramic-modified screw substrate prepared in step (3) to densify the pores on the surface and inside of the screw; (5) Depositing a SiC coating on the surface of the screw obtained in step (4) to obtain the ceramic-modified C / C composite material high-temperature screw product.
[0008] in: In step (1), the carbon fiber preform is prepared by three-dimensional puncture weaving or two-dimensional layered needle suture weaving.
[0009] The deposited pyrolytic carbon in step (1) adopts the CVI process, CH4 is used as the carbon source for CVI densification, the temperature is 1000 ℃~1200 ℃, the pressure in the CVI furnace is 1~2 kPa, the CVI densification cycle is 280~320 hours, and the apparent density of the obtained low-density C / C composite material is 1.25~1.35 g / cm 3 , pyrolytic carbon deposition is carried out under negative pressure conditions to achieve densification of the carbon fiber preform to obtain a low-density C / C composite material.
[0010] In step (2), the low-density C / C composite material obtained in step (1) is processed into a cylinder, and the diameter of the cylindrical C / C composite material is 16-18 mm and the height is 26-100 mm. Reducing the size of the C / C billet can reduce the resistance of the melt infiltration during the RMI process. The method of processing the low-density C / C composite material into a C / C cylinder is lathe turning.
[0011] Step (3), first burying the C / C cylinder in the alloy powder and placing it in a container, fully compacting the alloy powder so that the alloy powder is in full contact with the C / C cylinder, placing the container in a constant temperature zone of a vacuum heat treatment furnace to perform a high temperature reactive infiltration process (RMI) to obtain a ceramic-modified C / C cylinder. A graphite crucible can be used as a container in the RMI process.
[0012] The alloy powder in step (3) is MSi2, wherein M is Hf, Zr, Ti or Ta, the purity of the powder is 99.9%, and the particle size of the powder is below 325 mesh. The alloy powder reacts with the carbon matrix of the screw, namely the C / C cylinder, at high temperature to form MC-SiC composite phase ultra-high temperature ceramics. HfSi2, ZrSi2, TiSi2 and TaSi2 have similar physical and chemical properties, and their reaction mechanisms in the reaction infiltration process are completely consistent. The ultra-high temperature ceramic phases of HfC-SiC, ZrC-SiC, TiC-SiC and TaC-SiC can be introduced into the screw through the reaction infiltration step with the same process parameters.
[0013] The reaction temperature of the infiltration reaction in step (3) is 1700-1900°C, and the gas pressure in the vacuum heat treatment furnace is in a negative pressure state, and the gas pressure is not higher than 10 Pa.
[0014] In step (3), the modified C / C cylinder is processed into a standard screw by grinding. The cleaning step should be ultrasonicated in anhydrous ethanol for 10 minutes and placed in an electric hot air drying oven at 70°C for 12 hours for drying. The thread model of the processed standard screw base is M6~12, and the screw types include cylindrical head screws, countersunk screws, pan head screws, and hexagon socket screws.
[0015] In step (3), the C / C cylinder is placed in the graphite crucible container in a direction such that the two-dimensional preform needle-piercing direction and the three-dimensional preform puncturing direction of the C / C composite material are parallel to the bottom surface of the graphite crucible.
[0016] In step (4), the pyrolytic carbon is deposited using the CVI process. The temperature of the CVI densification process is 1000°C~1200°C, the gas pressure in the CVI furnace is 1~2 kPa, and the CVI densification cycle is 130~170 hours. The purpose is to seal and densify the surface of the screw.
[0017] In step (5), the SiC coating deposition process adopts a CVD process, the deposition temperature is 1100°C~1300°C, trimethylsilane is used as a reaction precursor, the CVD cycle is 3~5 hours, and the thickness of the prepared SiC coating is 20~40 μm.
[0018] The second object of the present invention is to provide a ceramic-modified C / C composite material high-temperature screw prepared by the above preparation method.
[0019] Compared with the prior art, the present invention has the following beneficial effects: The present invention proposes a method for preparing a C / C composite material high temperature screw resistant to 2000 ℃. By using the composite method of RMI, CVI and CVD, a highly uniformly distributed ultra-high temperature ceramic MC-SiC modified phase is sequentially introduced into the C / C screw matrix, wherein M is Hf, Zr, Ti or Ta, the C / C high temperature screw matrix is sealed and densified by CVI-PyC, and a SiC coating is prepared on the surface of the C / C high temperature screw matrix. The method has simple steps and a short preparation cycle, and can effectively avoid the problem that complex processes and multi-cycle cyclic heat treatment damage carbon fibers and cause serious degradation of mechanical properties. At the same time, the composite method of matrix modification and coating protection effectively improves the anti-ablation performance in an ultra-high temperature oxidation environment on the basis of ensuring the mechanical properties of the screw.
[0020] The C / C high temperature screw prepared by the preparation method has both excellent mechanical strength and ultra-high temperature anti-oxidation and ablation performance. The C / C high temperature screw prepared by the embodiment of the present invention has a shear strength of 30-40 MPa and a tensile strength of 78 MPa at the thread, showing excellent mechanical properties and service reliability. 2 After 60 s of Ar-H2 plasma ablation at 2000-3000 ℃, the structure remains intact without catastrophic damage, and the mass ablation rate is as low as 1.48~1.67×10 -2 g / s, showing excellent ultra-high temperature anti-oxidation and ablation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a schematic diagram of the process flow of preparing C / C high temperature screws according to the present invention; Figure 2 The macroscopic morphology photos of C / C high temperature screws prepared in the embodiments of the present invention, including: (a) 3D-C / C high temperature screw prepared in Example 1; (b) 2.5D-1-C / C high temperature screw prepared in Example 2; (c) 2.5D-2-C / C high temperature screw prepared in Example 3; Figure 3 The SEM photos of the microscopic morphology of the C / C high temperature screws prepared in the embodiments of the present invention. Among them: (a) 3D-C / C high temperature screw; (b) 2.5DC / C high temperature screw; Figure 4 The mechanical properties test results of the C / C high temperature screws prepared in the embodiment of the present invention. Among them: (a) shear strength; (b) tensile strength; Figure 5 The test results of the anti-ablation performance of the C / C high-temperature screws prepared in the embodiments of the present invention. Including: (a) The macroscopic morphology of the screw and its holding tooling; (b) The plasma ablation process of the screw; (c) The macroscopic morphology photos of the 3D-C / C high-temperature screw and the 2.5D-1-C / C high-temperature screw before and after ablation. DETAILED DESCRIPTION
[0022] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0023] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0024] like Figure 1 As shown, the steps of preparing the high temperature screws of the present invention are as follows: Step 1: The carbon fiber preform obtained by three-dimensional weaving is placed in the constant temperature zone of an isothermal chemical vapor infiltration (CVI) furnace, CH4 gas is used as the carbon source in the CVI densification process, and pyrolysis carbon deposition is performed under negative pressure conditions to achieve densification of the carbon fiber preform to obtain a low-density C / C composite material.
[0025] Step 2: Use a lathe to process the low-density C / C composite material obtained in step 1 into a cylinder, manually polish to remove broken fibers at the edges of the processed C / C cylinder, and thoroughly clean and dry the C / C cylinder.
[0026] Step 3: The C / C cylinder obtained in step 2 is buried in the alloy powder and placed in a graphite crucible, and is fully compacted to make the alloy powder fully contact with the C / C cylinder. The crucible is placed in the constant temperature zone of a vacuum heat treatment furnace for RMI reaction to obtain an ultra-high temperature ceramic-modified C / C composite material. Finally, the modified C / C cylinder is processed into a standard screw matrix.
[0027] Step 4: The prepared standard screw matrix is cleaned and dried, and carbonized and densified in a high-temperature negative pressure environment of an isothermal CVI furnace, and pyrolytic carbon (PyC) is introduced to seal the surface and internal pores of the C / C high-temperature screw matrix.
[0028] Step 5: Place the sample obtained in step 4 in the constant temperature zone of the CVD furnace, and prepare a SiC coating of a certain thickness on the surface of the C / C high-temperature screw substrate after sealing and densification in a high-temperature negative pressure environment, thereby obtaining the ceramic-modified C / C composite material screw described in the present invention.
[0029] The experimental raw materials used in the following examples and comparative examples of the present invention are all commercially available and are not further processed. The present invention is further described in detail below in conjunction with the accompanying drawings: Example 1 Step 1: Select two layers of 6K fiber non-woven fabric and one layer of 12K fiber mesh as the XY direction of the preform. The preform uses 3K carbon fiber double strands for bidirectional puncture in the Z direction with a puncture spacing of 2 mm. The size of the preform is compiled into 500×500×100 mm.
[0030] Step 2: Place the braided preform in the constant temperature zone of an isothermal chemical vapor deposition furnace, heat it to 1000 °C for negative pressure deposition, the pressure in the CVI furnace is 2 kPa, the CVI densification cycle is 280 hours, and the preform is densified to 1.3 g / cm 3 , and a low-density C / C composite blank was obtained. The C / C blank was then processed into a φ17×100 mm cylinder, and the fibers remaining at the corners of the cylinder due to machining were manually polished to remove them. The polished C / C cylinder was ultrasonically cleaned in anhydrous ethanol for 10 minutes to remove the graphite debris and oil stains remaining during the machining process, and then the C / C cylinder was placed in an electric hot air drying oven at 70 ℃ for 12 hours.
[0031] Step 3, placing the fully dried C / C cylinder in a graphite crucible, the puncture direction of the two-dimensional preform of the composite material of the C / C cylinder and the puncture direction of the three-dimensional preform are parallel to the bottom of the graphite crucible, filling the graphite crucible with ZrSi2 powder with a purity of 99.9% and a powder size of 325 mesh, and manually fully compacting the ZrSi2 powder to make close contact with the C / C cylinder. The crucible is placed in the constant temperature zone of a vacuum heat treatment furnace for a reaction infiltration process, evacuated to 5 Pa, and then the temperature of the constant temperature zone is increased to 1800 ° C at a heating rate of 5 ° C / min, and then slowly cooled with the furnace for 2 hours. During the reaction infiltration process, the vacuum pump is required to run continuously to ensure a vacuum environment. After the reaction infiltration process is completed, the C / C cylinder is taken out of the crucible, and the ZrSi2 hard block sticking to the surface of the C / C cylinder is manually polished to remove the ultra-high temperature ceramic ZrC-SiC modified C / C composite material. The modified C / C cylinder was processed into an M8 C / C screw matrix by a grinder. The C / C screw matrix was ultrasonically cleaned with anhydrous ethanol for 10 min and dried in an electric blast drying oven at 70℃ for 12 h to obtain a high-temperature oxidation-ablation-resistant C / C screw matrix modified with ultra-high temperature ceramic ZrC-SiC. The distribution uniformity of the modified ZrC-SiC ultra-high temperature ceramic phase in the C / C screw matrix was characterized by SEM ( Figure 3 ), the white ZrC phase and the gray SiC phase are highly uniformly distributed in all parts of the C / C screw matrix.
[0032] Step 4: Fix the modified C / C screw matrix on a double-layer porous graphite plate with a carbon rope and wrap the double-layer graphite plate with carbon felt, so that the axial direction of the C / C screw matrix is perpendicular to the graphite plate to facilitate the flow of CH4 gas and the regulation of the deposition flow field. Place the graphite plate with the C / C screw matrix fixed in an isothermal chemical vapor deposition furnace in a negative pressure environment of 1000 ° C to deposit PyC to fill the pores inside and on the surface of the C / C screw matrix.
[0033] Step 5: The C / C screw substrate after PyC sealing and densification is then placed in the constant temperature zone of the chemical vapor deposition furnace, and then evacuated to 4 kPa and pressure-maintained. If the airtightness is good, the temperature of the constant temperature zone is raised to 1100 °C at a heating rate of 5 °C / min, and methyltrichlorosilane (MTS) and H2 are introduced for deposition for 5 hours to form a 20 μm thick SiC coating. After cooling to room temperature, a C / C high-temperature screw coated with a SiC coating can be obtained, and the final density of the C / C high-temperature screw is 2.6 g / cm 3 .
[0034] The mechanical shear and plasma flame ablation resistance tests were carried out on the prepared C / C high temperature screws ( Figure 4 , Figure 5 The shear strength of the C / C high temperature screw thread is as high as 40.16 MPa, and the mass ablation rate of the C / C high temperature screw after 2000-3000 ℃ plasma flame ablation for 60 s is 1.48×10 -2 g / s, the C / C high temperature screw (referred to as 3D-C / C) prepared in this embodiment has both excellent mechanical strength and resistance to high temperature ablation at 2000 ℃. The shear strength of the screw thread was tested to be as high as 40.16MPa ( Figure 4 ).
[0035] Example 2 Step 1: Select five 1K fiber satin cloths and one layer of 12K fiber mesh as the XY direction of the preform. The Z direction of the preform adopts 3K carbon fiber single strand bidirectional needle stitching with a needle spacing of 6 mm. The size of the preform is compiled into 450×250×25mm.
[0036] Step 2: Place the braided preform in the constant temperature zone of an isothermal chemical vapor deposition furnace, heat it to 1000 °C for negative pressure deposition, the pressure in the CVI furnace is 1.5 kPa, the CVI densification cycle is 300 hours, and the preform is densified to 1.3 g / cm 3, and a low-density C / C composite blank was obtained. The C / C blank was then processed into a composite cylinder of φ17×8 mm and φ9×18 mm, and the fibers remaining at the corners of the composite cylinder due to machining were manually polished. The polished C / C composite cylinder was ultrasonically cleaned in anhydrous ethanol for 10 min to remove the graphite debris and oil stains remaining during the machining process, and then the C / C composite cylinder was placed in an electric hot air drying oven at 70 ℃ for 12 hours.
[0037] Step 3, placing the fully dried C / C composite cylinder in a graphite crucible, the two-dimensional preform puncture direction of the composite material of the C / C cylinder and the three-dimensional preform puncture direction are parallel to the bottom of the graphite crucible, filling the graphite crucible with ZrSi2 powder with a purity of 99.9% and a powder size of 325 mesh, and manually fully compacting the ZrSi2 powder to make close contact with the C / C composite cylinder. The crucible is placed in the constant temperature zone of a vacuum heat treatment furnace for a reaction infiltration process, evacuated to 5 Pa, and then the temperature of the constant temperature zone is increased to 1800 ° C at a heating rate of 5 ° C / min, and then slowly cooled with the furnace for 2 hours. During the reaction infiltration process, the vacuum pump is required to run continuously to ensure a vacuum environment. After the reaction infiltration process is completed, the C / C composite cylinder is taken out of the crucible, and the ZrSi2 hard block sticking to the surface of the C / C composite cylinder is manually polished to obtain an ultra-high temperature ceramic ZrC-SiC modified C / C composite material. The modified C / C composite cylinder was processed into an M8 C / C screw matrix by a grinder. The C / C screw matrix was ultrasonically cleaned with anhydrous ethanol for 10 min and dried in an electric blast drying oven at 70 ℃ for 12 h to obtain an ultra-high temperature ceramic ZrC-SiC modified high temperature oxidation and ablation resistant C / C screw matrix. The distribution uniformity of the modified ZrC-SiC ultra-high temperature ceramic phase in the C / C screw matrix was characterized by SEM ( Figure 3 ), the white ZrC phase and the gray SiC phase are highly uniformly distributed in all parts of the C / C screw matrix.
[0038] Step 4: Fix the modified C / C screw matrix on a double-layer porous graphite plate with a carbon rope and wrap the double-layer graphite plate with carbon felt, so that the axial direction of the C / C screw matrix is perpendicular to the graphite plate to facilitate the flow of CH4 gas and the regulation of the deposition flow field. Place the graphite plate with the C / C screw matrix fixed in an isothermal chemical vapor deposition furnace in a negative pressure environment at 1100 ° C to deposit PyC to fill the pores inside and on the surface of the C / C screw matrix.
[0039] Step 5: Place the C / C screw substrate after the deposited PyC sealing and densification in the constant temperature zone of the chemical vapor deposition furnace, then evacuate to 4 kPa and perform pressure treatment. If the airtightness is good, increase the temperature of the constant temperature zone to 1200 °C at a heating rate of 5 °C / min, introduce methyltrichlorosilane (MTS) and H2 for 5 hours, and form a 30 μm thick SiC coating. After cooling to room temperature, a C / C high-temperature screw coated with SiC coating can be obtained, and the final density of the C / C high-temperature screw is 2.35 g / cm 3 .
[0040] The mechanical shear and plasma flame ablation resistance tests were carried out on the prepared C / C high temperature screws ( Figure 4 , Figure 5 The shear strength of the C / C high temperature screw thread is as high as 31.72 MPa, and the mass ablation rate of the C / C high temperature screw after 2000-3000 ℃ plasma flame ablation for 60 s is 1.67×10 -2 g / s, the C / C high temperature screw (abbreviated as 2.5D-1-C / C) prepared in this embodiment has both excellent mechanical strength and resistance to high temperature ablation at 2000 ℃. The shear strength of the screw thread was tested to be as high as 31.72MPa ( Figure 4 ).
[0041] Example 3 Step 1: Select five 1K fiber satin cloths and one layer of 12K fiber mesh as the XY direction of the preform. The Z direction of the preform adopts 3K carbon fiber single strand bidirectional needle stitching with a needle spacing of 6 mm. The size of the preform is compiled into 450×250×25mm.
[0042] Step 2: Place the braided preform in the constant temperature zone of an isothermal CVI furnace, heat it to 1000 °C for negative pressure deposition, the pressure in the CVI furnace is 1 kPa, the CVI densification cycle is 320 hours, and the preform is densified to 1.3 g / cm 3 , and a low-density C / C composite blank was obtained. The C / C blank was then processed into a φ17×26 mm C / C cylinder, and the fibers remaining at the corners of the cylinder due to machining were manually polished to remove them. The polished C / C cylinder was ultrasonically cleaned in anhydrous ethanol for 10 min to remove the graphite debris and oil stains remaining during the machining process, and then the C / C cylinder was placed in an electric heated forced air drying oven at 70 ℃ for 12 hours.
[0043] Step 3, placing the fully dried C / C cylinder in a graphite crucible, the puncture direction of the two-dimensional preform of the composite material of the C / C cylinder and the puncture direction of the three-dimensional preform are parallel to the bottom of the graphite crucible, filling the graphite crucible with ZrSi2 powder with a purity of 99.9% and a powder size of 325 mesh, and manually fully compacting the ZrSi2 powder to make close contact with the C / C cylinder. The crucible is placed in the constant temperature zone of a vacuum heat treatment furnace for a reaction infiltration process, evacuated to 5 Pa, and then the temperature of the constant temperature zone is increased to 1800 ° C at a heating rate of 5 ° C / min, and then slowly cooled with the furnace for 2 hours. During the reaction infiltration process, the vacuum pump is required to run continuously to ensure a vacuum environment. After the reaction infiltration process is completed, the C / C cylinder is taken out of the crucible, and the ZrSi2 hard block sticking to the surface of the C / C cylinder is manually polished to remove the ultra-high temperature ceramic ZrC-SiC modified C / C composite material. The modified C / C cylinder was processed into an M8 C / C screw matrix using a grinder. The C / C screw matrix was ultrasonically cleaned with anhydrous ethanol for 10 min and dried in an electric forced air drying oven at 70 ℃ for 12 h to obtain a high temperature oxidation and ablation resistant C / C screw matrix modified with ultra-high temperature ceramic ZrC-SiC.
[0044] Step 4: Fix the modified C / C screw preform on a double-layer porous graphite plate with a carbon rope, and wrap the double-layer graphite plate with carbon felt so that the axial direction of the C / C screw matrix is perpendicular to the graphite plate to facilitate the flow of CH4 gas and the regulation of the deposition flow field. Place the graphite plate with the C / C screw matrix fixed in an isothermal CVI furnace in a negative pressure environment at 1200 °C to deposit PyC to fill the surface and internal pores of the C / C screw matrix.
[0045] Step 5, the C / C screw substrate after PyC sealing and densification is then placed in the constant temperature zone of the chemical vapor deposition furnace, and then evacuated to 4 kPa and pressure-maintained. If the airtightness is good, the temperature of the constant temperature zone is raised to 1300 °C at a heating rate of 5 °C / min, and methyltrichlorosilane (MTS) and H2 are introduced for deposition for 5 hours to form a 40 μm thick SiC coating. After cooling to room temperature, a C / C high-temperature screw coated with SiC coating (abbreviated as 2.5D-2-C / C) can be obtained. The final density of the C / C high-temperature screw is 2.31 g / cm 3 The shear test showed that the shear strength of the screw thread was as high as 31.48 MPa and the tensile strength was as high as 78.21 MPa ( Figure 4 ).
[0046] Test Case Figure 2The macroscopic morphology photos of the C / C high temperature screws prepared by the present invention, including: (a) 3D-C / C high temperature screw prepared in Example 1; (b) 2.5D-1-C / C high temperature screw prepared in Example 2; (c) 2.5D-2-C / C high temperature screw prepared in Example 3. It can be seen that the screws prepared in the three embodiments of the present invention have complete structures, and no obvious mechanical damage appears on the surface of the parts at a macroscopic scale. Due to the differences in the preform structure and the weaving method, the surface morphology of Example 1 is slightly different from that of Examples 2 and 3.
[0047] Figure 3 The SEM photos of the microscopic morphology of the C / C screw matrix prepared by the present invention are as follows: (a) 3D-C / C high-temperature screw matrix; (b) 2.5D-2-C / C high-temperature screw matrix. Through the microscopic morphology characterization of the edge, center, corners, and internal and edge parts of the thread of the C / C high-temperature screw head, it can be seen that although the preform structure of the 3D-C / C high-temperature screw prepared in Example 1 is different from that of the 2.5D-1-C / C high-temperature screw prepared in Example 2, the modified ceramic phase (white phase: ZrC, gray phase: SiC) introduced into the C / C matrix by the reaction infiltration process shows the characteristics of uniform distribution.
[0048] Figure 4 The test results of the shear strength of the C / C high temperature screws prepared in the present invention are shown in Figure 1. It can be seen that the shear strength of the C / C high temperature screws prepared in Examples 1 to 3 at the thread is higher than 30 MPa, among which the C / C high temperature screw 2.5D-2-C / C prepared in Example 3 has a tensile strength of up to 78.21 MPa, showing excellent mechanical strength and service reliability.
[0049] Figure 5 The results of the anti-ablation performance test of the C / C high-temperature screws prepared by the present invention. The results of the anti-ablation performance test of high-temperature screws: (a) Macromorphology of C / C high-temperature screws and their holding fixtures; (b) Plasma ablation process of C / C high-temperature screws; (c) Macromorphological photos of 3D-C / C high-temperature screws and 2.5D-1-C / C high-temperature screws before and after ablation. The C / C high-temperature screws prepared by the present invention were fixed with a C / C cylindrical fixture containing an M8 threaded hole, and the head of the C / C high-temperature screw was ablated for 60 s using a high thermal enthalpy plasma flame flow of 2000~3000 ℃. After ablation, the mass ablation rates of the 3D-C / C high-temperature screws and 2.5D-1-C / C high-temperature screws prepared in Examples 1 and 2 were both less than 0.02 g / s, showing excellent anti-ablation performance.
[0050] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a ceramic modified C / C composite material high temperature screw, characterized in that: The following steps are involved: (1) Depositing pyrolytic carbon on the carbon fiber preform obtained by weaving to obtain a low-density C / C composite material; (2) Cutting the low-density C / C composite material into C / C cylinders, grinding, cleaning and drying; (3) The C / C cylinder is placed in alloy powder for reaction infiltration to introduce multiphase ultrahigh temperature ceramics for modification, and then processed into a standard screw; (4) depositing pyrolytic carbon on the screw substrate prepared in step (3) to densify the pores on the surface and inside of the screw; (5) Depositing a SiC coating on the surface of the screw obtained in step (4) to obtain the ceramic-modified C / C composite material high-temperature screw product.
2. The method for preparing a ceramic-modified C / C composite material high-temperature screw according to claim 1, characterized in that: In the step (1), the carbon fiber preform is prepared by three-dimensional puncture weaving or two-dimensional layered needle suture weaving.
3. The method for preparing a ceramic-modified C / C composite material high-temperature screw according to claim 1, characterized in that: In the step (1), the pyrolytic carbon is deposited by a CVI process at a temperature of 1000°C to 1200°C, a pressure of 1 to 2 kPa in the CVI furnace, and a CVI densification cycle of 280 to 320 hours. The apparent density of the obtained low-density C / C composite material is 1.25 to 1.35 g / cm 3 .
4. The method for preparing a ceramic-modified C / C composite material high-temperature screw according to claim 1, characterized in that: In step (2), the diameter of the cylindrical C / C composite material is 16-18 mm and the height is 26-100 mm.
5. The method for preparing a ceramic-modified C / C composite material high-temperature screw according to claim 1, characterized in that: In the step (3), the C / C cylinder is first embedded in the alloy powder and placed in a container, fully compacted so that the alloy powder is in full contact with the C / C cylinder, and the container is placed in a constant temperature zone of a vacuum heat treatment furnace for infiltration reaction.
6. The method for preparing a ceramic-modified C / C composite material high-temperature screw according to claim 1 or 5, characterized in that: The alloy powder in step (3) is MSi2, and M is Hf, Zr, Ti or Ta.
7. The method for preparing a ceramic-modified C / C composite material high-temperature screw according to claim 1, characterized in that: The reaction temperature of the infiltration reaction in step (3) is 1700-1900°C, and the air pressure in the vacuum heat treatment furnace is in a negative pressure state, and the air pressure is not higher than 10 Pa.
8. The method for preparing a ceramic-modified C / C composite material high-temperature screw according to claim 1, characterized in that: The deposited pyrolytic carbon in step (4) adopts the CVI process, the temperature of the CVI densification process is 1000°C~1200°C, the gas pressure in the CVI furnace is 1~2 kPa, and the CVI densification cycle is 130~170 hours.
9. The method for preparing a ceramic-modified C / C composite material high-temperature screw according to claim 1, characterized in that: The SiC coating deposition process in step (5) adopts a CVD process, the deposition temperature is 1100°C~1300°C, trimethylsilane is used as the reaction gas, the CVD cycle is 3~5 hours, and the thickness of the prepared SiC coating is 20~40 μm.
10. A ceramic-modified C / C composite material high-temperature screw prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of high temperature resistant ceramic matrix composite screw
CN107021770A
Sandwich structure C / C ultrahigh-temperature ceramic composite material and preparation method thereof
CN113698223A